Complete genome sequence of Paludibacter propionicigenes type strain (WB4T). Issue 1 (January 2011) - Gronow, Sabine; Munk, Christine; Lapidus, Alla; Nolan, Matt; Lucas, Susan; Hammon, Nancy; Deshpande, Shweta; Cheng, Jan-Fang; Tapia, Roxane; Han, Cliff; Goodwin, Lynne; Pitluck, Sam; et al.
Abstract Paludibacter propionicigenes Uekiet al. 2006 is the type species of the genusPaludibacter, which belongs to the familyPorphyromonadaceae . The species is of interest because of the position it occupies in the tree of life where it can be found in close proximity to members of the genusDysgonomonas . This is the first completed genome sequence of a member of the genusPaludibacter and the third sequence from the familyPorphyromonadaceae . The 3, 685, 504 bp long genome with its 3, 054 protein-coding and 64 RNA genes consists of one circular chromosome and is a part of theG enomic E ncyclopedia of B acteria and A rchaea project.